UPAYA MENUMBUHKAN KREATIVITAS ANAK DENGAN PERMAINAN MATEMATIKA - achmad hidayatullah (Universitas Muhammadiyah Surabaya, 2016)
The development of more advanced affects parents. Most parents wished for her clever counting etc. Because demand is so great would be a problem if the expectations imposed on early childhood in a span of 2‐7 years. Educational institutions also as playgroup as the age of arithmetic that is not appropriate for children. Because on the one hand, early childhood, still in play. But both of them can’t be disputed and faced resistance. A Both of them can be bridged by their mathematical educational games in order to enhance the creativity of children. So in early childhood should be targeted not cognitive intelligence but the creativity of children. Therefore, this study will focus how to foster the creativity of children with math games. The approach in this study using literatif study. Is to find various references to give an answer to these problems. Keywords: Education, Creativity and Mathematics games